Hydrothermal carbonisation of digestate: an investigation into the technical design, economic feasibility and future potential of the process - Farthing, Sarah (2021)
Hydrothermal carbonisation (HTC) is an emerging technology used for the treatment of wet biomass. The process is carried out in an aqueous environment and so there are large thermal energy savings available for wet wastes that would ordinarily require drying prior to conventional thermochemical processes. HTC converts wet biomass into a solid product known as hydrochar, a process liquid and a small amount of CO2-rich process gas. The relative yields of the hydrochar and process liquid are influenced by process conditions. The products have potential markets as a fuel, fertiliser and/or for carbon sequestration. Currently, there are a number of industrial-scale HTC plants, but these typically operate under specific contractual agreements with local authorities or generators of problematic waste streams. In order to understand the potential of HTC in the wider market, there is the need for a robust and comprehensive analysis of the technical and economic performance of HTC. This will identify the conditions at which HTC is most feasible and allow for targeted support, development and deployment of the technology. This work comprised of an experimental analysis of the influence of HTC process conditions using various feedstocks, the development of a fully flexible process model validated by industrial data, and a detailed economic assessment and case study based in the UK. Digestate from the anaerobic digestion (AD) process was selected as the feedstock of focus for this work. In 2019 over 12.5 million tonnes of feedstock were processed with AD in the UK, generating 10.9 million tonnes of digestate by-product, equivalent to 500,000 tonnes on a dry basis. AD capacity and therefore digestate generation is increasing year on year, but issues remain for its use or disposal of digestate. The high moisture content, variable composition and restrictions on nutrient levels complicates and limits its spreading to agricultural land. There is a need for energy efficient, environmentally sound and economically viable treatment process. Current digestate management costs in the region of £16/tonne of digestate fibre, with a solids content of 25 wt.%, and it has been suggested that HTC could offer an overall lower-cost solution. This study is the first economic model of HTC using digestate as a feedstock. Three different digestate feedstocks were used experimentally: mixed food waste (waste-based), livestock slurry and silage (farm-based) and maize (crop-based). The hydrochar compositions reflected the feedstock used. The waste-based and farm-based hydrochars contained high levels of ash, often in the region of 30–50 wt.%, meaning they were deemed as unsuitable as solid fuel products. However, the hydrochar from the crop-based digestate had a carbon content of over 50 wt.% and ash content of below 10 wt.%, similar to bituminous coal. The waste-based and farm-based digestates and their resulting hydrochars had higher nutrient contents and so their use as a fertiliser or growing media was investigated. The results showed that they had promise in these areas, but more conclusive studies are required to understand the business case, especially concerning the presence of phytotoxic compounds and the long-term stability of the carbon. HTC experiments were carried out at a range of process conditions and it was found that temperature had the largest effect on the products, agreeing with existing literature results. A higher HTC temperature (of up to 250 °C) increased the degree of carbonisation, that is, an increased carbon content of the hydrochar but lower mass yield. The mass yield of hydrochar was typically measured as between 45 and 65 wt.% across all conditions. An increase in the initial feedstock moisture content was also found to increase the degree of carbonisation, although to a lesser degree than temperature. An increase in residence time was found to be statistically insignificant in nearly all cases. A process model was developed based on the experimental results and industrial HTC plant designs. This process model is the most detailed and accurate publicly available HTC model to date; it was designed with flexibility in mind along with industrial insights. A 2-reactor HTC plant treating 41,600 tonnes of digestate fibre with a solids content of 25 wt.% was found to require up to 1,000 MWh/year of electrical energy and 10,000 MWh/year of thermal energy. The capital expenditure (CAPEX) of a plant of this size came to below £5.8 million and the operating expenditure (OPEX) was in the region of £1.2 million. A 2-rector plant was found to be the best in terms of the trade-off between economies of scale and costs of transporting feedstock to site. The model results were validated with industrial data and were found to be in good agreement, offering a large improvement in data quality over what is currently publicly available in literature. There are two main revenue streams for a HTC plant treating digestate: the sale of hydrochar and the avoidance of digestate management costs. The sale price depended on the hydrochar properties. Crop-based hydrochar could expect to sell for up to £181/tonne as a solid fuel, whereas the hydrochar from waste-based and farm-based digestates could expect to be sold at £64–79/tonne as a fertiliser or £89–134/tonne in carbon sequestration. While there are a number of variables, in general, the farm-based and crop-based digestate showed better performance, with a payback period for the HTC plant of roughly 14 years or fewer. However, the HTC of waste-based digestate resulted in a payback period in excess of 20 years. A few lignocellulosic feedstocks were fed into the process and economic model for comparison. While they produced hydrochar of higher quality and yield, the high feedstock cost resulted in an economically unfeasible HTC model. With a fixed cost saving of avoiding current digestate fibre management practices of £16/tonne, the hydrochar sale price would need to be £255/tonne, £200/tonne or £190/tonne for the waste-based, farm-based and crop-based digestates, respectively, to achieve a pay-back period of 10 years. Alternatively, by fixing the hydrochar sale price at £150/tonne, the digestate savings would need to be £30/tonne, £26/tonne or £25/tonne of digestate fibre for a payback period of 10 years for the waste-based, farm-based and crop-based feedstocks, respectively. Ultimately, the HTC of farm-based and crop-based digestate showed promise both technically and economically, and so it is suggested as a possible treatment route in the UK. The waste-based digestate results were not as favourable. However, looking to the future, waste-based digestate has inherent problems with low quality and plastic contaminant content, both of which HTC can handle. Therefore, of the types of digestate considered here, its management costs are predicted to be the largest and most likely to increase. It is expected that under certain conditions and policy changes, it could become economically feasible in time. This study is the first to evaluate the techno-economics of the HTC of various digestate streams in the UK and set out the limits that must be met for it to be suggested as a treatment process.